Kolaborasi & Resistensi Identitas Kultural dalam Ekowisata Kayo Pulau di Kampung Tahima Soroma - Tommy O. Sibi; Simon Abdi K Frank; J. R. Mansoben (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the socio-cultural changes experienced by the Kayo Pulau community in response to ecotourism development promoted by the Jayapura City Government. Using a descriptive qualitative method, the research explores the community’s collaboration and resistance strategies in maintaining their cultural identity amidst tourism-driven modernization. Data were collected through in-depth interviews, participatory observation, and literature review involving 20 selected informants from various social backgrounds. The findings show that ecotourism has revitalized local cultural expressions and provided new economic opportunities while also triggering tensions, commodification of traditions, and symbolic identity shifts. Community responses are ambivalent: while some groups support ecotourism as a form of cultural affirmation and economic upliftment, others resist it subtly or overtly to preserve their ancestral values and spatial autonomy. This research highlights that identity is not a static heritage but a dynamic and negotiated process shaped by power relations, cultural pride, market demands, and ecological consciousness